Parâmetros de compressibilidade e permeabilidade ao ar de solos sob plantio direto - Mentges, Marcelo Ivan (2014)
The compaction process can be evaluated by soil compression curve. The curved segment of the compression curve shows the elastic deformation, while the linear segment represents the elastic deformation. The soil capacity to promoting adequate gas exchange between the root environment and the atmosphere affect plant growth and crop yield, thus showing the importance of quantifying properties related to soil ability to transmit oxygen to roots as key for the evaluation of soil physical quality. The general objective was to evaluate the effect of water content, soil structure and composition on the compressibility and air permeability of three Hapludox and one Paleudalf under no-tillage. Elastic and compressive properties, air permeability, physico-hydraulic properties, particle size and organic matter content were evaluated in soil samples equilibrated at 1, 3, 6, 10, 30, 50, 100, 300 and 500 kPa tensions. The water content along soybeans growing cycle was estimated by sequential hydrological balance and its effect on soil structural conditions was used for estimating soil bearing capacity and soil compactation susceptibility. Significant effect of the physical variables clay and soil organic matter content were observed in soil elasticity, while water content presented a reduced effect in such property. Greater clay and soil organic matter contents were associated to higher values of soil elasticity. The structural condition affects elasticity directly, mainly in sandy soils, while in loamy soils clay and organic matter contents have a larger influence on the soil elastic behavior. In sandy soils the effect of water content in soil compaction susceptibility is lower and it is most affect by soil density, while clay soils, because they retain more water, soil water content determined the compressive index variation along the management cicle. The models showed a satisfactory adjustment when the compression index was estimated, while the capacity of estimation precompaction pressure was lower for all soils. The adaption of Busscher s model for estimating soil precompaction pressure, despite the low reliability, showed that soil load bearing capacity varies along the management cycle and that sandy soils are more resistant to compactation that clay soils. The compaction effects on soil air permeability is realted mainly to air-filled porosity and soil pore continuity, independently on water content that affects adversely air permeability. In sandy soils air permeability increases as soil water content decreases is larger, compared to loamy soils. In soils cultivated under no-tillage, water content effect on air permeability is associated with greater quantity and continuity of soil pores available for airflow to occur.